2018
DOI: 10.1016/j.brat.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Dismantling Mindfulness-Based Cognitive Therapy: Creation and validation of 8-week focused attention and open monitoring interventions within a 3-armed randomized controlled trial

Abstract: Background While mindfulness-based interventions (MBIs) employ two distinct practices, focused attention (FA) and open monitoring (OM), the integrated delivery of these practices in MBIs precludes understanding of their practice-specific effects or mechanisms of action. The purpose of this study is to isolate hypothesized active ingredients and practice-specific mechanistic target engagement by creating structurally equivalent interventions that differ only by the active ingredient (meditation practice) offere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 114 publications
0
84
0
Order By: Relevance
“…To test whether learning acceptance skills is a critical emotion regulation mechanism of mindfulness interventions for improving affective, stress, and social relationship outcomes, recent studies have employed intervention dismantling designs. Dismantling designs have been recommended and used to identify active treatment elements of multi-component mindfulness interventions (33,34). We have adopted this experimental approach to test whether removing acceptance skills training from mindfulness interventions reduces or eliminates treatment-related improvements in emotion regulation-relevant outcomes.…”
Section: Testing Mat: Dismantling Acceptance From Mindfulness Intervementioning
confidence: 99%
“…To test whether learning acceptance skills is a critical emotion regulation mechanism of mindfulness interventions for improving affective, stress, and social relationship outcomes, recent studies have employed intervention dismantling designs. Dismantling designs have been recommended and used to identify active treatment elements of multi-component mindfulness interventions (33,34). We have adopted this experimental approach to test whether removing acceptance skills training from mindfulness interventions reduces or eliminates treatment-related improvements in emotion regulation-relevant outcomes.…”
Section: Testing Mat: Dismantling Acceptance From Mindfulness Intervementioning
confidence: 99%
“…A pilot study comparing MBCT in group and individual therapy showed significant symptom improvement in individual MBCT that was equally strong as in group MBCT (Schroevers, Tovote, Snippe, & Fleer, ). However, this study investigated the effects of the whole MBCT package and did not directly target the mindfulness exercise component (Britton et al, ). Furthermore, a meta‐analysis showed that mindfulness exercises as a stand‐alone intervention have beneficial effects on anxiety and depression in healthy subjects (Blanck et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in a novel study published this year, Britton and colleagues observed that mindfulnessbased interventions (viz., MBSR and MBCT) employ two distinct practices, namely, focused attention (FA) and open monitoring (OM) [78]. These two meditation practices were identified previously by Lutz and associates [79] as being central to mindfulness-based programs.…”
Section: Review Of Models Of Mindfulness Efficacymentioning
confidence: 95%